Conference – 1992 Equation

λ t N ( υ λ t , σ λ t 2 ) = g ( λ t ) , MathType@MTEF@5@5@+= feaagKart1ev2aaatCvAUfeBSjuyZL2yd9gzLbvyNv2CaerbuLwBLn hiov2DGi1BTfMBaeXatLxBI9gBaerbd9wDYLwzYbItLDharqqtubsr 4rNCHbGeaGqiVu0Je9sqqrpepC0xbbL8F4rqqrFfpeea0xe9Lq=Jc9 vqaqpepm0xbba9pwe9Q8fs0=yqaqpepae9pg0FirpepeKkFr0xfr=x fr=xb9adbaqaaeGaciGaaiaabeqaamaabaabaaGcbaGaeq4UdW2aaS baaSqaaiaabshaaeqaaOGaeSipIOJaamOtamaabmaabaGaeqyXdu3a aSbaaSqaaiabeU7aSjaabshaaeqaaOGaaiilaiabeo8aZnaaDaaale aacqaH7oaBcaqG0baabaGaaGOmaaaaaOGaayjkaiaawMcaaiabg2da 9iaabEgadaqadaqaaiabeU7aSnaaBaaaleaacaqG0baabeaaaOGaay jkaiaawMcaaiaacYcaaaa@4E1F@